2021
DOI: 10.1021/acsestwater.1c00159
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Induced Intensification of Electrochemical Treatment of Bulk Drug Pharmaceutical Wastewater

Abstract: This study was carried out to intensify the electrochemical treatment of bulk drug pharmaceutical wastewater (BDW) using ultrasound. The effects of the operating parameters on chemical oxygen demand (COD) and total organic carbon (TOC) removal efficiency were studied using a response surface methodology-based central composite design. Under optimum conditions that included an ultrasonic power of 67 W, a current density of 173 A m–2, an initial pH of 4.5, and an interelectrode distance of 0.5 cm, COD and TOC re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Figure S17 suggested that the oxidation ability in the cathode region mainly resulted from • OH and SO 4 •– , but • OH was the key contributor. Based on these results, a schematic of the REM–persulfate system for contaminant oxidation is shown in Figure S18, mainly including (1) direct contaminant oxidation on the Ti 4 O 7 REM anode surface via DET, (2) indirect oxidation by • OH/SO 4 •– generated by Ti 4 O 7 REM anode and the CAPO process at Ti 4 O 7 REM cathode, and (3) indirect oxidation by active chlorine species in the presence of Cl – . , Considering the results from EPR (Figure S14) and quenching experiments (Figures S16 and S17) as well as the high TOC removal of the RO concentrate samples of pretreated coking wastewater (Figure a), indirect oxidation by • OH may play a key role in oxidizing organics in the REM–persulfate system. See Text S7 for the detailed description of the results of EPR and quenching studies and the proposed mechanism for contaminants oxidation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure S17 suggested that the oxidation ability in the cathode region mainly resulted from • OH and SO 4 •– , but • OH was the key contributor. Based on these results, a schematic of the REM–persulfate system for contaminant oxidation is shown in Figure S18, mainly including (1) direct contaminant oxidation on the Ti 4 O 7 REM anode surface via DET, (2) indirect oxidation by • OH/SO 4 •– generated by Ti 4 O 7 REM anode and the CAPO process at Ti 4 O 7 REM cathode, and (3) indirect oxidation by active chlorine species in the presence of Cl – . , Considering the results from EPR (Figure S14) and quenching experiments (Figures S16 and S17) as well as the high TOC removal of the RO concentrate samples of pretreated coking wastewater (Figure a), indirect oxidation by • OH may play a key role in oxidizing organics in the REM–persulfate system. See Text S7 for the detailed description of the results of EPR and quenching studies and the proposed mechanism for contaminants oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…•− generated by Ti 4 O 7 REM anode and the CAPO process at Ti 4 O 7 REM cathode, and (3) indirect oxidation by active chlorine species in the presence of Cl − . 37,38 Considering the results from EPR (Figure S14) and quenching experiments (Figures S16 and S17) as well as the high TOC removal of the RO concentrate samples of pretreated coking wastewater (Figure 4a), indirect oxidation by • OH may play a key role in oxidizing organics in the REM−persulfate system. See Text S7 for the detailed description of the results of EPR and quenching studies and the proposed mechanism for contaminants oxidation.…”
Section: Mechanisms For Contaminant Oxidation In the Rem−persulfate S...mentioning
confidence: 97%
“…The prevalence of the ammonium ion at pH levels below 6 indicates that radical oxidation can be an effective technique for the efficient degradation of ammonia. Consequently, an increase in H 2 O 2 concentration from 0 to 5 mmol/L reduces ammonia removal, possibly due to a scavenging effect caused by the reaction of excess H 2 O 2 with HO (Patidar and Srivastava, 2021). When the pH rises above 6, the primary mechanism for the elimination of free volatile ammonia via ultrasound is revealed.…”
Section: Integrated Hydrogen Peroxide Sono and Heterogeneous Photocat...mentioning
confidence: 99%
“…However, incomplete degradation/mineralization, higher chemical requirement, secondary waste generation, pH adjustment before effluent discharge, and high treatment costs limit these methods for scale-up studies and further optimization. Ultrasound-assisted remediation such as sono-electrochemical (US-EC), 11 sono-electro-Fenton-Fe 2 O 3 (SF), 12 sono-photocatalytic, 13 and sono-electro-Fenton (SEF) 14 has been reported to be environment-friendly, in situ generation of ROS chemical-free, use of electron as a green reagent, and easy to operate techniques. These approaches have been reported for the adequate mineralization of the various persistent organic pollutants (POPs), i.e., ofloxacin (OFL), 15 ciprofloxacin, 16 ibuprofen (IBF), 17 and formic acid, 18 without secondary problems such as sludge generation, discharge of effluents, etc.…”
Section: Introductionmentioning
confidence: 99%